PENGARUH DISKUSI KELOMPOK UNTUK MENURUNKAN STRES PADA MAHASISWA YANG SEDANG SKRIPSI - Rohmah, Faridah Ainur (HUMANITAS (Jurnal Psikologi Indonesia), 2006)
AbstrakThe purpose of  this research was to investigate the effectiveness of  group discussion thatgiven to minimize stress of  students writing thesis. The subjects were students of  the Faculty ofPsychology, Ahmad Dahlan University in Yogyakarta, working on their thesis. They volunteeredto participate in the research. There were 18 students who were randomly divided into twogroups. Nine were joining group discussion and the other nine were in the control group. Thisstudy performed by with pre-test and post-test control measurement toward scale of stress. Thesubjects stress before, after the treatment, and one month after treatment were measured.The process of  the experiment was observed and recorded with video tape recorder.The data were analyzed quantitatively and qualitatively. The quantitative data were analyzedwith t-test. The data from the observational record, interview, and self  report from the subjectswere analyzed qualitatively. The result show that: there is not difference in stress between thediscussion group and the control group (t=-3,67, p>0,05).Keywords : group discussion, stress